Bercerita Di Era Digital : Pengaruh Digital Storytelling Terhadap Pembentukan Karakter Islami Siswa - Fina Lestari; Revi Ayu (Science and Education Journal (SICEDU), 2026)
In the digital era, Islamic Religious Education is required to adapt to technological developments in order to create learning experiences that are engaging, interactive, and meaningful. One innovation that can be implemented is the digital storytelling method as a medium for delivering learning materials. This study aims to determine the effect of the digital storytelling method on students’ Islamic character at [name of school/research location]. This study employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of [number of students] students selected using [sampling technique]. Data were collected through an Islamic character questionnaire administered before and after the treatment. The digital storytelling videos were selected and adapted to the learning materials and obtained from the YouTube platform. The data were analyzed using descriptive analysis, correlation analysis, and the coefficient of determination. The results showed an improvement in students’ Islamic character, with the mean pretest score increasing from 27.3 (54.6%) to 36.7 (73.4%) on the posttest. The analysis showed a correlation coefficient (R) of 0.652 and an R Square value of 0.425. These findings indicate a fairly strong relationship between the digital storytelling method and students’ Islamic character, with 42.5% of the variation in Islamic character explained by the research model. Thus, digital storytelling has the potential to serve as an innovative alternative in Islamic Religious Education to support the development of students’ Islamic character.